Subclinical atherosclerosis and increased risk of hearing impairment. Issue 2 (February 2015) - Fischer, Mary E.; Schubert, Carla R.; Nondahl, David M.; Dalton, Dayna S.; Huang, Guan-Hua; Keating, Brendan J.; Klein, Barbara E.K.; Klein, Ronald; Tweed, Ted S.; Cruickshanks, Karen J.
Abstract: Objective : The study's purpose was to test if subclinical atherosclerosis was associated with the risk of developing HI in a large cohort of middle-aged participants. Methods : Study subjects were members of the Beaver Dam Offspring Study (BOSS), a longitudinal study of adult children of participants in the population-based Epidemiology of Hearing Loss Study (1993-present). BOSS examinations took place in 2005–2008 (baseline) and 2010–2013 (5-year follow-up). The 5-year incidence of hearing impairment was defined as a pure-tone average (PTA) of thresholds at 0.5, 1, 2 and 4 kHz > 25 dB Hearing Level (dB HL) in either ear at follow-up among participants at risk (baseline PTA in both ears < = 25 dB HL; n = 2436, mean age = 47.7 years). Atherosclerosis was measured as the mean carotid intima-media thickness and the presence of carotid artery plaque. Results : Among the 1984 participants at-risk with a follow-up audiometric examination, the 5-year incidence of hearing impairment was 8.3% (95% Confidence Interval (C.I.) 7.1, 9.5). With multivariable adjustment, carotid intima-media thickness was positively associated with hearing impairment incidence (Relative Risk (RR) = 1.14 per 0.1 mm, 95% C.I. 1.04, 1.24). The number of sites (0–6) with plaque was also positively associated with the incidence of impairment (RR = 1.16 per site, 95% C.I. 1.01, 1.32). Conclusion : Atherosclerosis was associated with the 5-year incidence of hearing impairment in this predominantly middle-aged cohort. Interventions targeting atherosclerosis prevention may help to prevent or delay the onset of hearing impairment. Highlights: Strategies targeting modifiable risk factors for hearing impairment are needed. We investigated subclinical atherosclerosis and 5-year risk of hearing impairment. Study population was primarily middle-aged. Risk of hearing impairment increased about 15% in presence of atherosclerosis.